2018
DOI: 10.1038/s41594-018-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of DNA double-strand-break repair using novel single-molecule forceps

Abstract: Repairing DNA double-strand breaks (DSBs) by non-homologous end-joining (NHEJ) requires multiple proteins to recognize and bind DNA ends, process them for compatibility, and ligate them together. We constructed novel DNA substrates for single-molecule nano-manipulation allowing us to mechanically detect, probe, and rupture in real-time DSB synapsis by specific human NHEJ components. DNA-PKcs and Ku allow DNA end synapsis on the 100 ms timescale, and addition of PAXX extends this lifetime to ~2s. Further additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 44 publications
(53 reference statements)
7
98
0
Order By: Relevance
“…16,17 This construct still interacts with XRCC4 and promotes minimal end joining in in vitro reconstitution assays. 12,16,34 Within human cells, the XLF C-terminal tail was reported to be dispensable for V(D)J recombination. 35 As we observe a substantial reduction in NHEJ efficiency in mESCs upon removal of either the tail or KBM, this result may reflect a differential requirement of intermolecular interactions during V(D)J recombination as compared to spontaneous DSB repair.…”
Section: Recruitment Of Xlf To Dsbs Is Necessary But Not Sufficient Fmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 This construct still interacts with XRCC4 and promotes minimal end joining in in vitro reconstitution assays. 12,16,34 Within human cells, the XLF C-terminal tail was reported to be dispensable for V(D)J recombination. 35 As we observe a substantial reduction in NHEJ efficiency in mESCs upon removal of either the tail or KBM, this result may reflect a differential requirement of intermolecular interactions during V(D)J recombination as compared to spontaneous DSB repair.…”
Section: Recruitment Of Xlf To Dsbs Is Necessary But Not Sufficient Fmentioning
confidence: 99%
“…7,10 Importantly, the catalytic activity of Lig4 is not required to form the SR complex, demonstrating that the ligase plays a structural role in end synapsis. 10,11 Subsequent biochemical reconstitutions of human NHEJ proteins also found evidence for these two synaptic states, 12 suggesting that the architecture of the NHEJ synaptic complex is conserved from Xenopus to humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using single-molecule Forster resonance energy transfer (smFRET) imaging, we previously showed that synapsis occurs in two stages ( Figure 1A) (Graham et al, 2016): initially, Ku and DNA-PKcs form a "long-range" synaptic complex, in which dye-labeled DNA ends are tethered at a distance greater than that required for FRET (>100 Å);; subsequently, DNA-PKcs kinase activity, XLF, and Lig4-XRCC4 convert the long-range complex into a high-FRET "short-range" complex in which ends are held close together in a ligation-competent state. Stable synapsis of DNA ends using purified human proteins shows similar requirements (Wang et al, 2018). Conflicting models have been proposed in which end processing occurs independently of synapsis (Lieber, 2010;, while ends are synapsed ; Waters et al, 2014b), or upon dissolution of synapsis after failed ligation .…”
Section: Introductionmentioning
confidence: 94%
“…NHEJ is used to repair double-strand DNA breaks (DSBs) that arise due to V (D) J recombination, ionizing radiation, and reactive oxygen species, without the need for a template DNA. The first step in NHEJ involves binding of Ku70-Ku80 heterodimers to both ends of a DNA break [32,33], followed by the recruitment and activation of the catalytic subunits of DNA dependent protein kinase (DNA-PKcs) [34,35]. DNA end processing involves phosphorylation of nucleases such as Artemis, and DNA polymerases to replace damaged bases; followed by ligation of blunt DNA ends by the XLF-XRCC4-DNA ligase IV complex.…”
Section: Introductionmentioning
confidence: 99%